Spatially resolved and polarization resolved electroluminescence of 1.3 μm InGaAsP semiconductor diode lasers - Peters, Hudson Frank (My University, 1991)
A technique for obtaining maps of the spatially-resolved and polarization-resolved electroluminescence of 1.3 μm semiconductor diode lasers has been developed. It reveals information about the strain, scattering and absorption which exist in the active region of lasers. These data have been correlated with the spectral output of the lasers, and models have been developed which explain the correlation.
Keywords: Engineering Physics; Other Engineering; Other Engineering